Total Uterine Inversion Post Partum: Case Report and Management Strategies - Anthony Paulo Sunjaya; Andriana Kumala Dewi, MD, Sp.OG (Tehran University of Medical Sciences, 2019)
Objective: Total Uterine Inversion is a rare obstetric emergency that may lead to hypovolemia and eventually death. Its incidence varies between different populations and is reported to be between 1 in 2000 to 1 in 50,000 births. This article describes a case of acute total uterine inversion post-partum and review of its management strategies. Case report: A primigravid 24 year old female 1.5 hours post-partum was referred to the emergency department from the community health center with total uterine inversion and hypovolemic shock. The patient had given birth vaginally with a midwife. We successfully performed manual reposition of the uterus and balloon tamponade was placed to stop the hemorrhage. Conclusion: Total Uterine Inversion is a rare but potentially deadly complication post-vaginal delivery. Its low incidence leads to sparse experience among health professionals in managing this obstetrical emergency. Early fluid resuscitation, manual reposition and balloon tamponadeis essential in order to obtain the best prognosis.Further studies are required to determine the most optimal conservative and surgical management for uterine inversion.